Added Value and Profitability of PT ABC’s Processed Moringa Products - Sonia Ghinaa Salim; Bayu Krisnamurthi; Nia Rosiana (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
The utilization of Moringa in food processing, herbal medicine, and animal feed makes this plant attractive to researchers for testing its effectiveness and entrepreneurs for making it a business commodity. PT ABC is one of the companies processing Moringa into various derivative products. PT ABC is the largest company in Central Java, establishing Blora as the centre of the Moringa commodity. The untapped potential of Moringa, with its high economic value, has driven the government to aspire to make Moringa an icon of Blora Regency, allowing the community to capitalize on it as a business commodity. This study analyzes the added value and profitability of Moringa Capsule and Moringa Infusion products. Applying the Hayami method, the analysis identifies Moringa Capsules as having a higher added value ratio than Moringa Infusions. Profitability assessments, encompassing production costs, break-even points, and operational efficiency, confirm that both products generate substantial profits. The company operates above the break-even point, with profitability of IDR 64,529 for capsules and IDR 22,387 for infusions. These findings reveal the economic potential of Moringa-based products with profitability margins of 30.97 per cent for Moringa Capsule and 15.35 per cent for Moringa Infusions. These margins highlight the viability of expanding production and tapping into new markets. Blora can strengthen its competitiveness in national and international markets by promoting innovation in product development. Practical implications include diversifying product offerings to meet evolving consumer demands and leveraging profitability data to attract investment, ultimately enhancing rural incomes and economic resilience.